Factors influencing constructive conflict management style of nursing interns: a structural equation modeling approach based on the self-determination theory - Yang Xiong; Zhuo-er Huang; Wei-lian Peng; Ya-qian Fu; Zhuo-heng Li; Yi-hua Chen; Bi-rong Liu; Qi-feng Yi; Wen-jun Chen (BMC Nursing)
Abstract Background Improving nursing interns’ behavioral patterns toward the constructive conflict management style is critical for promoting effective nurse-patient conflict resolution. However, there is a dearth of research on the factors that influence constructive conflict management styles guided by theoretical principles. Aim To explore the relationships among nursing interns’ constructive conflict management style, career-related social support, emotional intelligence, and communication ability with angry patients using self-determination theory. Methods We conducted a cross-sectional study following STROBE guidelines and recruited 375 nursing interns from 31 universities at a comprehensive teaching hospital in Hunan Province. Data on general information, career-related social support, emotional intelligence, communication ability with angry patients, and constructive conflict management style was collected from nursing interns using a general information questionnaire and reliable scales. Structural equation modeling was used to model and test the hypothesis. Results The nursing interns’ career-related social support had a significant immediate impact on constructive conflict management style (β = 0.320, CI: 0.099–0.213). Career-related social support and constructive conflict management style were mediated by emotional intelligence (β = 0.088, CI: 0.010–0.081) and communication ability with angry patients (β = 0.098, CI: 0.023–0.078), respectively. While multiple mediating effects (β = 0.067, CI: 0.014–0.057) were found. Conclusion High levels of professional social support, emotional intelligence, and communication ability with angry patients positively influence constructive conflict management style, especially social support. In order to promote the constructive conflict management style of nursing interns, nursing educators and managers should emphasize the establishment and maintenance of career support systems, and use experiential teaching methods such as role playing, virtual reality scenario simulation, and peer mentoring.